2018
DOI: 10.1007/s00592-018-1109-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of megakaryocytes as a target of advanced glycation end products in diabetic complications in bone marrow

Abstract: Diabetic condition in animals might exert its influence on hematopoiesis via megakaryocytes-the newly identified modulator of hematopoietic stem cells in bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This appears to be a plausible explanation since microvascular damage in DM is likely to impact perfusion to the bone marrow as well as abnormal levels of cytokines related to widespread inflammation in DM [ 61 , 67 , 68 ]. Notably, some evidence shows that the accumulation of advanced glycation end products (AGEs) in DM can also influence hematopoiesis in the bone marrow [ 69 ]. Whether or not this mechanism directly affects RBC progenitors is unknown.…”
Section: Multifactorial Mechanisms Of Rbc Dysfunction and Anemia In D...mentioning
confidence: 99%
“…This appears to be a plausible explanation since microvascular damage in DM is likely to impact perfusion to the bone marrow as well as abnormal levels of cytokines related to widespread inflammation in DM [ 61 , 67 , 68 ]. Notably, some evidence shows that the accumulation of advanced glycation end products (AGEs) in DM can also influence hematopoiesis in the bone marrow [ 69 ]. Whether or not this mechanism directly affects RBC progenitors is unknown.…”
Section: Multifactorial Mechanisms Of Rbc Dysfunction and Anemia In D...mentioning
confidence: 99%
“…It has been shown that two different models of diabetes in rats show different phenotypes of platelet response . Also, recently published report on alterations in profile of protein expression in megakaryocytes and platelet generation in STZ‐induced diabetic and in ob/ob diabetic mice revealed that these two models differ in this aspect . It implicates that platelet hyperreactivity in diabetes is a complex phenomenon, which is influenced by a plethora of factors which vary with the type of diabetes and its associated alterations.…”
Section: Discussionmentioning
confidence: 99%
“…How diabetes influences expression of COX‐1 in platelets remains to be elucidated. It has been recently published that bovine serum albumin modified by advanced glycation end products significantly altered expression of certain proteins including platelet factor 4 in cultured megakaryocytes . It suggests that long‐term hyperglycaemia can indirectly affect protein profile in platelets produced by megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%